EMPLOYING MALE ANNIHILATION OR BAIT APPLICATION TECHNIQUES TO SUPPRESS THE PEACH FRUIT FLY, BACTROCERA ZONATA (DIPTERA: TEPHRITIDAE) - MUNIR, H; AHMAD, S; CHATTHA, MB; MAHMOOD, R; TARIQ, MR; IQBAL, M; ASHRAF, S (Biological and Clinical Sciences Research Journal, 2023)
Guava (Psidium guajava) is one of the important crops of tropical regions and a major source of antioxidants and fibers. Peach fruit fly (PFF) Bactrocera zonata is a pest of many fruit crops like guava. The purpose was to extract the most efficient method among MAT, BAT, or Botanicals by considering their mortality in 24, 48, 72, and 96-hour intervals. In both BAT and Botanicals, the efficiency of extracts of Neem (A. indica), Moringa (Moringa oleifera), Citrus, and Parthenium (Parthenium hysterophorus) at concentrations (100%, 50%, and 25%) was observed. We placed 39 traps in the field with 4 different treatments, 3 concentrations having 3 replicates along with control. Maximum mortality after 24 hours at 100% concentration of Neem was 69.91% and minimum mortality (13.91%) was observed at 25% concentration of Parthenium. While mortality ranged for A. indica (58.12% - 31.78%), M. oleifera (44.01 - 22.68), Citrus (40.21 - 19.67) and P. hysterophorus (34.11 - 13.91). Citrus and moringa showed moderate mortality. In the present study, the percentage of mortality was much higher at the highest concentration of neem when compared with the control treatment. The study revealed that all the measures gave satisfactory results and proved to be more efficient, while botanicals were least significant.